In Vitro Digestibility and Fermentability of Complete Feeds as Affected by Vitamin Supplementation - Grewal, R.S.; Wadhwa, M.; Bakshi, M.P.S. (Indian Journal of Animal Nutrition, 2018)
The study was taken up to assess the effect of different vitamins on in vitro digestibility and fermentability of complete feeds at different metabolisable energy (ME) levels. Two iso-nitrogenous diets containing 10% (MME) and 20% (HME) higher ME than recommended (NRC, 2001) were formulated. Both the diets contained low rumen undegradable protein (LUDP; @ 24% of dietary CP). The complete feeds were supplemented with different vitamins either individually (niacin, biotin or vitamin E) or in different combinations (niacin and biotin; niacin and vitamin E; biotin and vitamin E; niacin, biotin and vitamin E) in 2 Ã— 8 factorial design. Biotin, vitamin E and niacin were supplemented @ 1.33, 10.67 and 533 mg/kg DM of complete feed, respectively. The effect of ME levels in complete feed, irrespective of vitamins revealed that the net gas production (NGP), digestibility of true OM (P<0.05) and NDF and ME availability were improved significantly (P<0.01) in HME-LUDP diet as compared to MME-LUDP diet. Supplementing the complete feeds with niacin, biotin or vitamin E individually irrespective of ME levels did not have any significant effect on the above parameters but niacin and vitamin E combination improved (P<0.05) NGP, digestibility of true OM and ME availability as compared to control diet or diet supplemented with biotin or vitamin E alone. However, the above parameters were comparable to control and combination of biotin + vitamin E or niacin + biotin + vitamin E supplemented groups indicating that biotin may not have any additional benefit in improving in vitro digestibility of nutrients and availability of ME. It was concluded that combination of niacin and vitamin E supplementation improved the in vitro utilization of complete feed.